2008
DOI: 10.1111/j.1365-2389.2007.00997.x
|View full text |Cite
|
Sign up to set email alerts
|

Increasing pH releases colloidal lead in a highly contaminated forest soil

Abstract: Colloids can play an important role in the leaching of lead (Pb) in soils, and liming to increase pH may produce conditions conducive to colloid release. We studied the effect of pH and the role of counterion valency on the mobilization of Pb in two topsoil horizons of a former shooting range. In batch experiments, the release of both dissolved and colloidal Pb was studied at a pH range between 3 and 7. The pH was adjusted with solutions of nitric acid (pH 3) and KOH and Ca(OH) 2 (pH 4-7) and the chemical comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 35 publications
2
26
0
1
Order By: Relevance
“…Even though the stability of colloids according to pH is well documented, little studies were dedicated to the understanding of the detachment of organic colloids and associated TE release from soils with regard to pH change. In these studies, pH was evidenced to control the mobilization of organic colloids in soils [37,38]. This mobilization enhancement might be explained by the increasing negative surface charges of colloids with increasing pH [14,[39][40][41].…”
Section: Introductionmentioning
confidence: 92%
“…Even though the stability of colloids according to pH is well documented, little studies were dedicated to the understanding of the detachment of organic colloids and associated TE release from soils with regard to pH change. In these studies, pH was evidenced to control the mobilization of organic colloids in soils [37,38]. This mobilization enhancement might be explained by the increasing negative surface charges of colloids with increasing pH [14,[39][40][41].…”
Section: Introductionmentioning
confidence: 92%
“…Colloidalsized particles binding with P species can migrate through immobile solid particles via effects of dispersion, striping and straining (Hens and Merckx 2001). Therefore, the P coll is more likely to migrate a longer distance and deliver to the receiving water (Heathwaite et al 2005;Klitzke et al 2008;Siemens et al 2008), which had been deemed as a new indicator of evaluating P loss potential in some studies (Ilg et al 2005). Besides, according to reaction abilities with molybdate reagent, molybdenum reactive P (MRP) and molybdenum unreactive P (MUP) are distinguished.…”
Section: Responsible Editor: Chengrong Chenmentioning
confidence: 98%
“…4b). That may be caused by the presence of surface adsorbed organic matter, which masked the inorganic mineralogy (Kjaergaard et al 2004;Klitzke et al 2008). The SEM-EDS mapping scanning results showed that the corresponding maps of Ca, Mg, Fe, Si, and C exhibited the same trend in the P-rich zones (see Fig.…”
Section: P Coll Distribution At Low Phmentioning
confidence: 99%
“…Mobilization of colloids sufficient to allow colloid-facilitated P transport usually requires an environmental perturbation, such as changes in pH, ionic strength, and soil water content (Bunn et al 2002). Soil pH change could significantly influence contaminant transport (Moreira et al 2008), and also the colloid-facilitated P mobility by destroying the inorganic and organic cement of potentially mobilized matrix fines, or cause stronger repulsion by the negatively charged soil matrix and decrease of inter-particle attraction (Klitzke et al 2008). Laboratory experiments have demonstrated that low pH mobilized colloids by inducing the dissolution of inorganic cementing phases, mainly Al and Fe oxides, and clay content (Ryan and Gschwend 1994;Swartz and Gschwend 1998;Slowey et al 2005).…”
Section: Introductionmentioning
confidence: 98%